New Delay-Analysis Method Using Modified Schedule and Modified Updated Schedule for Construction Projects - Cevikba, Murat; Okudan, Ozan; Isik, Zeynep (ASCE-AMER SOC CIVIL ENGINEERS, 2022)
Being one of the most common dispute causes in construction projects, the delay is extremely important to be resolved promptly. To resolve delay-related disputes, delay analysis that is conducted to determine the amount of the delay that has occurred on a project together with its contractual responsible party is of paramount importance. Notwithstanding the numerous enhancements in the delay analysis domain, delay resolution remains one of the most challenging issues in construction projects due to various drawbacks of existing delay analysis methods. To minimize the delay-related issues in construction projects, this study, therefore, aims to develop a new delay analysis method that overcomes the drawbacks of existing delay analysis methods. The drawbacks of current methods were initially determined via an in-depth literature review and a focus group discussion (FGD) session conducted with seven experts experienced in the delay analysis domain. This step revealed that most of these methods ignore some critical features, such as consideration of critical path (CP), actual progress data, and fluctuations on CP. Moreover, most of the methods lack detailed numerical procedures and consider only the owner's delay. Furthermore, some types of activity relationships, actual improvements, and further delays made by contractors on the planned excusable compensable delay (ECD) and excusable noncompensable delay (END) are usually ignored by these methods. Then, a new delay analysis method, namely modified schedule versus modified updated schedule (MSvsMUS), was developed. To overcome the detected drawbacks, the proposed method is designed and developed in a way that can consider various activity relationships among the critical activities, include detailed numerical equations, and compute the variations between the modified schedule (MS) including planned fragnet/s and modified updated schedule (MUS) including actualized fragnet/s periodically. This was then followed by a case study conducted to demonstrate the method's mechanism. Finally, the developed method was evaluated and validated by conducting a second FDG session and a hypothetical case study. Results demonstrated that MSvsMUS has considerable potential to resolve delays and delay-related disputes escalated in construction projects.
Keywords: Delay analysis; Extension of time; Claim; Modified schedule (MS); Modified updated schedule (MUS); Baseline schedule; FOCUS GROUP; INDUSTRY; COST; FLOAT; Construction & Building Technology; Engineering